Gold nanoparticles decorated on carbon nanotube modified screen-printed electrode for flow injection amperometric determination of methyldopa - Jantima Upan (2019)
© 2019, All Right reserved. Gold nanoparticles (AuNPs) decorated on multi-walled carbon nanotubes (MWCNTs) were used as a modifier on the surface of a screen-printed carbon electrode (SPCE) for sensitive determination of methyldopa, which is widely used as an antihypertensive medicine. The electrochemical oxidation of methyldopa on the modified electrode was carried out in flow injection amperometric (FI–amp) system at the applied potential of +400 mV vs Ag/AgCl. As a result, SPCE modified with 20%w/w of gold nanoparticles on carbon nanotube (AuNPs-CNT/SPCE) provided an excellent sensitivity to methyldopa detection. Morphology of AuNPs-CNT was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), and x-ray diffraction (XRD), which indicated a proper distribution of AuNPs on CNT and high electrode areas. Several parameters that affect the response of the modified electrode were studied. The plot of peak height versus methyldopa concentration showed a linear range of 0.2-100 μM with a detection limit of 0.1 μM. The proposed flow injection amperometric system was successfully applied for methyldopa determination in real samples.